SPORT TYPE AND BASELINE NEUROCOGNITIVE SCORES AMONG HEALTHY HIGH SCHOOL ATHLETES - Oldham, Jessie R. (Orthop J Sports Med, 2021)
BACKGROUND: Athletes who participate in collision sports may experience more repetitive head impacts than other sport types. These repetitive head impacts have been theorized as a potential catalyst for cognitive problems later in life. It is unknown, however, if sport type influences neurocognitive performance. HYPOTHESIS/PURPOSE: Our purpose was to investigate the association between sport type and baseline neurocognitive scores in a high school athletic population. We hypothesized that athletes participating in collision sports would demonstrate worse scores on baseline neurocognitive tests compared to those in contact or non-contact sports. METHODS: We conducted a cross-sectional, observational study using baseline computerized neurocognitive scores of 186,117 high school student-athletes (age: 15.47±2.28 years, height: 168.53±10.77 cm, weight: 63.02±14.83 kg, 45% female) in the state of Massachusetts. The dependent variables were five composite scores (verbal memory, visual memory, visual motor, reaction time, and impulse control) and total symptom score. The independent variables included sport type (collision, contact, non-contact), age, sex, and concussion history. We used univariable one-way ANOVAS to compare composite scores between sport type. We conducted a series of multivariable regression models, controlling for age, sex, and number of previous concussions, to examine the independent association between sport type and composite scores. RESULTS: There was a minimal but statistically significant association between sport type and composite scores, with collision sport athletes performing slightly worse than other athletes on most composite scores. Collision sport athletes had a slightly lower symptom burden. (Tables 1 and 2) CONCLUSION: While statistically significant, the differences in neurocognitive function and symptom burden between sport type are of questionable clinical significance. In fact, all of them fall within the reliable change index values of each respective score. As participants were in high school at the time of the study, we cannot determine the potential for associations later in life. TABLES/FIGURES: